2014
DOI: 10.4236/pp.2014.51004
|View full text |Cite
|
Sign up to set email alerts
|

The Adenosine Receptor Agonist 5’-<i>N</i>-Ethylcarboxamide-Adenosine Increases Glucose 6-Phosphatase Expression and Gluconeogenesis

Abstract: Intraperitoneal administration of the non-selective adenosine receptor agonist 5'-N-ethylcarboxamide-adenosine (NECA) (0.1 or 0.3 mg/kg) increased fasting serum glucose levels in mice. To clarify the mechanism responsible for this, the expression of liver glucose 6-phosphatase (G6Pase: a gluconeogenic enzyme) was analyzed, and it was found that G6Pase mRNA was increased by NECA treatment. Administration of 0.3 mg/kg NECA resulted in elevated serum glucose levels at 1 h and were further elevated at 6 h. Adminis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Seven experiments were performed using the NECA treatment. Details of the NECA treatment methods have been described previously [19]. Briefly, after the fasting period, mice were intraperitoneally (i.p.)…”
Section: Animal Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Seven experiments were performed using the NECA treatment. Details of the NECA treatment methods have been described previously [19]. Briefly, after the fasting period, mice were intraperitoneally (i.p.)…”
Section: Animal Treatmentsmentioning
confidence: 99%
“…We previously reported that the non-specific adenosine receptor agonist 5'-N-ethylcarboxamide-adenosine (NECA) increased serum glucose levels and the expression of a glucogenic enzyme (glucose 6-phosphatase) in the liver [19] [20]. Based on the dose of NECA administered in these studies and plasma concentrations after the administration of other adenosine agonists [21], it was inferred that the serum NECA concentration was in the μM range and also that NECA activated adenosine A2b receptors.…”
Section: Introductionmentioning
confidence: 99%